2021
DOI: 10.3390/genes12030385
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin and Mineral Supplementation and Rate of Maternal Weight Gain Affects Placental Expression of Energy Metabolism and Transport-Related Genes

Abstract: Maternal nutrients are essential for proper fetal and placental development and function. However, the effects of vitamin and mineral supplementation under two rates of maternal weight gain on placental genome-wide gene expression have not been investigated so far. Furthermore, biological processes and pathways in the placenta that act in response to early maternal nutrition are yet to be elucidated. Herein, we examined the impact of maternal vitamin and mineral supplementation (from pre-breeding to day 83 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 74 publications
1
29
0
Order By: Relevance
“…Considering the current evidence, it is important to explore whether bovine maternal nutrition/microbiome during pregnancy influences feto-maternal crosstalk, subsequently influencing offspring microbiome development. Maternal vitamin and mineral supplementation before calving has been well documented to be associated with improved fetal programming and offspring health and productivity in cattle (Mee et al, 1995; Wilde, 2006; Van Emon et al, 2020; Diniz et al, 2021; Menezes et al, 2021). However, whether VTM supplementation-associated positive outcomes observed pre- and post- calving are dependent on alterations in the ruminal microbiota remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the current evidence, it is important to explore whether bovine maternal nutrition/microbiome during pregnancy influences feto-maternal crosstalk, subsequently influencing offspring microbiome development. Maternal vitamin and mineral supplementation before calving has been well documented to be associated with improved fetal programming and offspring health and productivity in cattle (Mee et al, 1995; Wilde, 2006; Van Emon et al, 2020; Diniz et al, 2021; Menezes et al, 2021). However, whether VTM supplementation-associated positive outcomes observed pre- and post- calving are dependent on alterations in the ruminal microbiota remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used 16S rRNA gene sequencing to characterize the nasopharyngeal, ruminal and vaginal microbiota of virgin yearling heifers from dams given different nutritional diets during their first trimester of gestation, and in pregnant beef heifers in response to direct feeding of a mineral and vitamin (VTM) supplement during the first 6 months of gestation. Of note, a well-defined positive impact of maternal VTM supplementation exists on offspring health and performance in beef cattle, and the role of VTM on fetal programming assessed during the first trimester of pregnancy have been documented (Mee et al, 1995; Wilde, 2006; Van Emon et al, 2020; Diniz et al, 2021; Menezes et al, 2021). Questions remain, however, pertaining to whether these maternal VTM supplementation-associated positive outcomes are dependent on VTM-induced alterations of ruminal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we used 16S rRNA gene sequencing to characterize the nasopharyngeal, ruminal and vaginal microbiota of virgin yearling heifers from dams given different nutritional diets during their first trimester of gestation, and in pregnant beef heifers in response to direct feeding of a mineral and vitamin (VTM) supplement during the first 6 months of gestation. Of note, a well-defined positive impact of maternal VTM supplementation exists on offspring health and performance in beef cattle, and the role of VTM on fetal programming assessed during the first trimester of pregnancy have been documented [25][26][27][28][29]. Questions remain, however, pertaining to whether these maternal VTM supplementation-associated positive outcomes are dependent on VTM-induced alterations of ruminal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…This is a limitation of the study, as individual intake restriction could not be confirmed. Recently, mineral supplementation has been implicated to aid placental adaptations in beef heifers when offered pre- and post-breeding [ 55 ]. Our data do not reflect these findings when mineral supplementation begins in late gestation, as no differences in placental efficiency were observed between S+ or S− pregnancies ( p = 0.31).…”
Section: Resultsmentioning
confidence: 99%
“…Because the allantois is the site of fetal waste deposition until the last ~20 days of gestation [ 56 ], this lack of microbial diversity may in fact be reflective of the fetal gut microbiome, which may contribute microbes to the allantois throughout gestation. Overall, the lack of microbial diversity observed in FR placentae implicate a less robust microbiome, which may interact in unknown ways with metabolic markers and signaling pathways affecting fetal health [ 55 ].…”
Section: Resultsmentioning
confidence: 99%